Fast dynamic ventilation MRI of hyperpolarized 129Xe using spiral imaging. Issue 5 (16th September 2017) - Doganay, Ozkan; Matin, Tahreema N.; Mcintyre, Anthony; Burns, Brian; Schulte, Rolf F.; Gleeson, Fergus V.; Bulte, Daniel
Abstract : Purpose: To develop and optimize a rapid dynamic hyperpolarized 129 Xe ventilation (DXeV) MRI protocol and investigate the feasibility of capturing pulmonary signal‐time curves in human lungs. Theory and Methods: Spiral k‐space trajectories were designed with the number of interleaves N int  = 1, 2, 4, and 8 corresponding to voxel sizes of 8 mm, 5 mm, 4 mm, and 2.5 mm, respectively, for field of view = 15 cm. DXeV images were acquired from a gas‐flow phantom to investigate the ability of N int  = 1, 2, 4, and 8 to capture signal‐time curves. A finite element model was constructed to investigate gas‐flow dynamics corroborating the experimental signal‐time curves. DXeV images were also carried out in six subjects (three healthy and three chronic obstructive pulmonary disease subjects). Results: DXeV images and numerical modelling of signal‐time curves permitted the quantification of temporal and spatial resolutions for different numbers of spiral interleaves. The two‐interleaved spiral ( N int  = 2) was found to be the most time‐efficient to obtain DXeV images and signal‐time curves of whole lungs with a temporal resolution of 624 ms for 13 slices. Signal‐time curves were well matched in three healthy volunteers. The Spearman's correlations of chronic obstructive pulmonary disease subjects were statistically different from three healthy subjects ( P  < 0.05). Conclusion: The N int  = 2 spiral demonstrates the successful acquisition of DXeV images and signal‐time curves in healthy subjects and chronic obstructive pulmonary disease patients. Magn Reson Med 79:2597–2606, 2018. © 2017 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.